Effectiveness and cost of contraception in France (FACET study): a cohort study from the French National Healthcare Insurance Database. (October 2018) - Agostini, Aubert; Godard, Chloé; Laurendeau, Caroline; Benmahmoud, Amel; Lafuma, Antoine; Doz, Marianne; Lévy-Bachelot, Laurie; Gourmelen, Julie; Linet, Teddy
Abstract: Objective: To assess the effectiveness and costs associated with contraceptive methods based on real-world data in France. Study design: A cross-sectional cohort study based on data from a representative sample of the French National Healthcare Insurance Database ( Echantillon Généralistes des Bénéficiaires (EGB)) was performed between January 1st 2006 and December 31st 2012. Women aged 15 years or older and users of at least one reimbursed contraceptive method between January 1st 2012 and December 31st 2012 were selected. The outcome of interest was unintended pregnancy, defined as pregnancies occurring after at least one month since the dispensation of a contraceptive method. The mean annual costs of contraceptive methods (in 2012 Euros) were collected in the database from a health system perspective. Costs were expressed for the first year of use, considering the next years of use and taking into account or not the cost of unplanned pregnancies. Results: A population of 48, 090 women representative of the 4, 664, 730 French women with a reimbursed contraceptive method was identified in the EGB in 2012: 68.6% used at least one reimbursed oral contraception (OC), 30.2% used at least one intrauterine devices (IUD) (LGN-IUS 52 mg, 17.6%; copper, 13.1%) and 5.1% used at least one etonogestrel implant. Unplanned pregnancies rates ranged from 0.6% with LNG-IUS 52 mg and 0.8% with the etonogestrel implant to 4.8% with 1st and 2nd generation combined OCs. The mean annual costs of contraception for the first year of use ranged from €145 for 1st-2nd generation combined oral contraceptions (COCs) to €308 for LNG-IUS 52 mg taking into account the next years of use, the etonogestrel implant was associated with the lowest mean annual cost (€88). When costs of unplanned pregnancies were taken into account, the mean annual cost of contraception for the first year of use was lower for progestin-only OC (€251) and copper IUD (€257) compared to etonogestrel implant (€300) and LNG-IUS 52 mg(€323). Conclusion: This real-world study suggests that Long-acting reversible contraceptives (LARCs) (i.e. implant and IUDs) should be considered for a broader use to prevent unplanned pregnancies and related abortions in France both from a public health and economic perspective.